2020
DOI: 10.1111/jace.17290
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of Lu2‐xCexTi2O7 pyrochlores under 400 keV Ne irradiation

Abstract: Lu2‐xCexTi2O7 (LCTO) pyrochlores were irradiated by 400 keV Ne2+ with fluences (dose) of up to 5 × 1015 ions/cm2 (1.875 dpa). The detailed damage process was investigated by combining grazing incident angle X‐ray diffraction (GIXRD) and transmission electron microscopy (TEM). Subsequent to the 2% volume swelling at a fluence of 1 × 1014 ions/cm2 (0.037 dpa), the initially swollen LCTO pyrochlore formed both a disordered fluorite phase and a nanocrystalline pyrochlore phase at a fluence of 5 × 1014 ions/cm2 (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Two typical defect formation mechanisms in pyrochlore are reported in studying the phase transitions in pyrochlores under pressure: The first one is the cation position swap to form anti-situ defects, which leads to A 3+ and B 4+ cation disorder, the second defect formation mechanism is that the 48f oxygen ions move to 8b oxygen vacancies to form Frenkel defect pairs, which leads to anion-lattice disorder and a pyrochlore phase transition [8,25]. Similar phase transition mechanisms are also found in studies of irradiation [33][34][35][36], high temperatures [37] in pyrochlore.…”
Section: Introductionsupporting
confidence: 55%
“…Two typical defect formation mechanisms in pyrochlore are reported in studying the phase transitions in pyrochlores under pressure: The first one is the cation position swap to form anti-situ defects, which leads to A 3+ and B 4+ cation disorder, the second defect formation mechanism is that the 48f oxygen ions move to 8b oxygen vacancies to form Frenkel defect pairs, which leads to anion-lattice disorder and a pyrochlore phase transition [8,25]. Similar phase transition mechanisms are also found in studies of irradiation [33][34][35][36], high temperatures [37] in pyrochlore.…”
Section: Introductionsupporting
confidence: 55%
“…It was found that the ordered pyrochlore structure first transforms into an anion-disordered pyrochlore structure and at higher fluences into a cation-disordered fluorite structure [47] . Recently, Xia et al [48] reported the interesting case of ion irradiation related recrystallization processes at higher fluences in Lu 2-x Ce x Ti 2 O 7 pyrochlore phases. Janish et al [49] investigated in-situ the recrystallization of an irradiated pyrochlore phase using transmission electron microscopy.…”
Section: Introductionmentioning
confidence: 99%